2008
DOI: 10.1080/03091900701781317
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heart rate variability derived from finger-tip photoplethysmography as compared to electrocardiography

Abstract: Heart rate variability (HRV) is traditionally derived from RR interval time series of electrocardiography (ECG). Photoplethysmography (PPG) also reflects the cardiac rhythm since the mechanical activity of the heart is coupled to its electrical activity. Thus, theoretically, PPG can be used for determining the interval between successive heartbeats and heart rate variability. However, the PPG wave lags behind the ECG signal by the time required for transmission of pulse wave. In this study, finger-tip PPG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(199 citation statements)
references
References 12 publications
9
189
0
1
Order By: Relevance
“…Previous studies comparing PRV derived from PPG and ECG under optimal rest conditions did not report significant differences in PRV assessment. 6,45,46 However, studies that compared PPG and ECG under less optimal conditions have shown that PRV PPG assessed the parameters of short-term variability (HF, RMSSD, and SD1) considerable less reliable compared to ECG. 7,9 In line with these findings, our results showed that the cold temperature change (COLD) exhibited significant increases of the parameters reflecting short-term variability (i.e., HF activity, RMSSD, and SD1), whereas the parameters reflecting long-term variability did not change significantly compared to the control condition (CONTROL).…”
Section: Sympathetic and Parasympathetic Autonomous Nervous System Comentioning
confidence: 99%
“…Previous studies comparing PRV derived from PPG and ECG under optimal rest conditions did not report significant differences in PRV assessment. 6,45,46 However, studies that compared PPG and ECG under less optimal conditions have shown that PRV PPG assessed the parameters of short-term variability (HF, RMSSD, and SD1) considerable less reliable compared to ECG. 7,9 In line with these findings, our results showed that the cold temperature change (COLD) exhibited significant increases of the parameters reflecting short-term variability (i.e., HF activity, RMSSD, and SD1), whereas the parameters reflecting long-term variability did not change significantly compared to the control condition (CONTROL).…”
Section: Sympathetic and Parasympathetic Autonomous Nervous System Comentioning
confidence: 99%
“…PRV analysis has been performed in multiple studies using PPG signals recorded from the finger or earlobe and report varying levels of accuracy compared to HRV (2,4,5,7,8,15,21). By comparison to ECG signals, PPG waveforms are characteristically smooth and do not contain a clearly defined and detectable 'landmark' feature.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal characteristics of PPG are studied using the peak-to-peak intervals among pulses. These intervals have been shown to correspond directly to the inter-peak intervals of ECG [22], and hence can be characterized using well-known ECG inter-beat features [14]. These include temporal features such as mean and standard deviation of heart rate and frequency domain features such as LF/HF ratio.…”
Section: Background and Related Workmentioning
confidence: 99%